Father Guy Mary-Rousselière (1913-1994) - Gordon, Bryan C. (ARCTIC, 1994)
Father Guy Mary-Rousselière was 81 when he died in a house fire in Pond Inlet in April. Born in Le Mans, France, Father Mary-Rousseliere obtained a philosophy degree at the seminary of St. Sulpice, Paris in 1931, taking his first vows for the priesthood in the same year. He came to Canada a year after his ordination as an Oblate of Mary Immaculate in 1937, beginning his work with the Dene in northern Saskatchewan and Manitoba, and later ministering to the Inuit of Repulse, Pelly and Hudson bays, and Baffin Island. He told me that his 56 years in the North, with 36 years at Pond Inlet, had been rewarding as a priest. Father Mary-Rousselière was foremost a priest, but ever curious about the prehistory of the people he served. He learned much about Chipewyan and Inuit language and culture, later identifying their early tools and describing their past. . Father Mary-Rousselière gave of himself in many ways. Archaeologists Hans Muller-Beck and Susan Rowley, and archaeology students from other countries visited or worked at Nunguvik or Saatut. He helped me in my Barrenland research by identifying Oblate archives as early sources of birth dates for my seasonality studies. Mary-Rousselière was a member of the Northwest Territories Historic Sites and Monuments Board for many years. His long years of scholarly service in the Arctic were publicly acknowledged when the Honourable Bill McKnight, Minister of Indian Affairs and Northern Development, presented him with the Northern Science Award in 1988. .